Analisa Pengelolaan Lingkungan Gedung X Terhadap Kualitas Udara dan Air - Putri Redita Rositasari; Rizka Novembrianto (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Air quality and air are very important for human health and comfort. Good quality air can ensure enough oxygen for the human body, while good quality water can meet the water needs of the human body and other needs. However, the quality of air and water in some places can be disrupted by various factors, such as air and water pollution, and poor environmental management. Therefore, it is important to conduct research on air and water quality to determine their level of cleanliness and take the necessary action to maintain or improve it. This research aims to analyze the air and water quality in Building X, as well as the factors that affect it, so that it can provide useful information for maintaining good air and water quality. The research method used is a document study that begins with conducting a critical review of the evaluation matrix for environmental management efforts in the Environmental Impact Assessment Document of Building X in Sleman District. The results of the study show that the environmental management of buildings affects the air and water quality inside. Good management can ensure the quality of air and water that is healthy and comfortable for building occupants, and help reduce negative impacts on the environment